Pengaruh Motif Hedonis Dan Browsing Terhadap Pembelian Impulsif Pada Pembelian Online Produk Fashion - Prihatini, Roro Agung; Susanto, Susanto (Universitas Muhammadiyah Yogyakarta, 2015)
The purpose of this research is to identify the influence of hedonic motive and browsing toward implusive buying on online purchasing fashion product. The subject of the research is consument coming from varsity student in Yogyakarta that buy fashion product toward e-commerce company. This research use purposive sampling technique to collect the data. From the survey, the researcher gain 100 person as the respondent. Next, the data will be analyze by using the Structural Equation Modeling (SEM).The result of the research showed that the hedonic motive has a positive influence towards the impulsive buying. It also has positive influence in browsing, while browsing does not have any influence towards impulsive buying. Hence, the other results showed that browsing does not have any influence to be a mediator between hedonic motive and impulsive buying.